PENGELOLAAN SAMPAH POPOK SEKALI PAKAI UNTUK KESADARAN LINGKUNGAN: STUDI KASUS DI DESA CIAMBAR - Nurhayati; Fatmawati, Ravena; Amelia, Aliah; Armaninata, Eka Nabila; Cinthya Martin, Gracia; Astono, Diazahra; Roffi Abdullah Syafi’i, Muhammad; Ayomi, Valdis (Jurnal Pengabdian Masyarakat Sabangka, 2025)
This community service program aimed to increase awareness and skills of residents in managing disposable diaper waste in Ciambar Village, Sukabumi. The program was carried out in two main sessions: an educational session on the importance of maintaining a healthy environment and a practical session on recycling diapers into planting media. The method applied was a participatory approach involving 28 participants, consisting of PKK members, Posyandu cadres, and village officials, ensuring that the activities were truly aligned with community needs. During the educational session, participants gained understanding of the negative impacts of diaper waste on health and the environment if not properly managed. In the practical session, participants were directly engaged in processing diaper waste into environmentally friendly and useful planting media. The results of the program indicated improvements in participants’ knowledge and skills, as well as the growth of collective awareness to reduce pollution. This program strengthens the community’s role in preserving the environment while supporting the achievement of Sustainable Development Goals (SDGs) at the village level.